Food for thought: refereeing and data - Guvener, A. (Soccer America, 2017)
Refereeing in the UEFA competitions seem to reflect the European league norms. The refereeing in MLS seems to be close to the European norms in terms of fouls called, yellow cards and red cards. It is a bit closer to EPL norm, which is not surprising. Unlike some commentators who want to think that in MLS too few cards are shown, the averages show that PRO officials are doing a job which is close to global norms.